TANDA DALAM ARTIKEL â€œ2018 IN PHOTOS: WRAPPING UP THE YEARâ€ - Rumambi, Revita; Rambing, Rosalina R.; Manus, Jeane A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTÂ This research which entitled â€œTanda dalam Artikel 2018 in Photos: Wrapping Up the Yearâ€ is focused on sign that can be found in a news photo. The aims of this research are to identify and classify kinds of sign and to analyze and describe meaning of a sign that can be found in news photo. This research uses Pierceâ€™s Theory in the process of identifying and classifying kinds of sign and the process of analyze and describe the meaning of a sign. The source of news photo was taken from an article which is entitled 2018 in Photos: Wrapping Up the Year, published by The Atlantic on their website at www.theatlantic.com. The method of this research is descriptive method. Every sign that can be found in a news photo will be identified and classified into three kinds of sign which are index, icon, and symbol. Then, every sign meaning will be analyzed and described according to the process called semiosis. The result of this research shows that three kinds of sign which are index, icon, and symbols can be found in twenty selected photos, and every sign meaning from each sign found in twenty selected photos are different from each other.___________________________________ Keywords: semiotic analysis, sign, kinds of sign, news photo